Implementasi SPK Karyawan Terbaik Metode A-Hirarki Proses dan S-Additive Weighting - Wawan Taufiq Wawan; Supriyanto Supriyanto; Sidik Rahmatullah (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2023)
PT. Puncak Menara Hijau Mas Kotabumi is an industrial company engaged in the wood processing business. This company processes wood into 4 kinds of materials which are ready to be supplied to Java Island and some are exported to Japan. The 4 types of processed wood produced are Sawntimber ex KD, S4S (4-sided shaved), Plywood and Furniture. In order to increase the quality of decisions, decision support systems combine various intelligence sources. We use 2 methods, namely AHP and SAW, weight  Criteria1 16%, Criteria 2 33%, Criteria 3 13%, Criteria 4 11%, Criteria 5 6%,, Criteria 6 17%, Criteria 7 4% The final result of the employee who is given the best predicate is Alternative 47 with a rank of 2,049 . So that the employee is entitled to get a prize/bonus as the best employee